Association of pain and clinical factors on disability and quality of life in systemic sclerosis: A cross-sectional study from Turkish League Against Rheumatism Network - Remzi Çevik; Serda Em; Kemal Nas; Murat Toprak; Gizem Cengiz; Mustafa Çalış; İlhan Sezer and Ayşe Ünal Enginar and Pınar Bora Karslı and Sinem Sağ and et al. (Archives of Rheumatology, 2023)
Objectives: In this study, we aimed to evaluate the factors associated with disability and quality of life (QoL) in Turkish patients with systemic sclerosis (SSc). Patients and methods: Between January 2018 and January 2019, a total of 256 SSc patients (20 males, 236 females; mean age: 50.9±12.4 years; range, 19 to 87 years) who were diagnosed with SSc were included in the study. Disability and health-related QoL (HRQoL) were evaluated by the Health Assessment Questionnaire (HAQ), scleroderma HAQ (SHAQ), Duruöz Hand Index (DHI), and Short Form-36 (SF-36). Linear regression analysis methods were used to describe factors associated with disability and QoL of the patients. Results: All disability scores were higher and HRQoL scores were lower in diffuse cutaneous SSc patients compared limited cutaneous SSc, and differentiations were significant (p=0.001 and p=0.007). In multiple regression, pain (VAS) was the strongest predictor for high disability and low QoL scores (p<0.001) as HAQ (β=0.397, 0.386, 0.452), SHAQ (β=0.397, 0.448, 0.372), DHI (β=0.446, 0.536, 0.389), PCS (β=-0.417,-0.499, -0.408) and MCS (β=-0.478, -0.441, -0.370) in combined, lcSSc and dcSSc patients respectively. The factors associated with high disability and low QoL scores were forced vital capacity for HAQ (β=-0.172, p=0.002) and SF-36 PCS (β=0.187, p=0.001); disease duration for HAQ (β=0.208, p<0.001), DHI (β=0.147, p=0.006), and SF-36 PCS (β=-0.134, p=0.014); 6-minute walk test for HAQ (β=-0.161, p=0.005) and SF-36 PCS (β=0.153, p=0.009); and modified Rodnan skin score for SHAQ (β=0.250, p<0.001) and DHI (β=0.233, p<0.001) in SSc patients. Diffusing capacity of the lungs for carbon monoxide for HAQ (β=-0.189, p=0.010) and SHAQ (β=-0.247, p=0.002); erythrocyte sedimentation rate for DHI (β=0.322, p<0.001); age for SF-36 PCS (β=-0.221, p=0.003) and body mass index for SF-36 PCS (β=-0.200, p=0.008) and MCS (β=-0.175, p=0.034) were the other variables associated with high disability or low QoL scores in SSc subsets. Conclusion: Clinicians should consider the management of the pain and its sources as a key to improve better functional state and quality of daily life in SSc.